Economic integration in a cross border perspective - An emerging new system of production? - Andreas P. Cornett (European Regional Science Association (ERSA), 2005)
The economic development of regions is today closely determined by the linkages and networks to external partners as well as their own Hinterlands. Main focus in this paper is on issues related to changes in the system of production, in regional as well as international, and a cross border perspective. Empirically the analysis is based on results from a project analyzing regional development in the Baltic Sea Regions. Issues addressed are spatial impacts of alterations in the economic linkages in the BSR since the transition process started in the aftermath of the break down of the iron curtain. Theoretically the concepts applied are based on economic integration and location. An analytical framework is sketched in the first part of the paper. The second section provides a brief introduction to the economic development in the regions considered, including an assessment of cross border flows, i.e. trade and FDI. Part three is devoted to an analysis of changes in the regional production system with regard to manufacture, and the implication for regional economic performance and employment in the out-sourcing regions as well as in in-sourcing regions. In addition, the issue of 're-outsourcing' is addressed. The latter deals with western companies considering moving production facilities out of the BSR region into areas with lower production costs. The final section summarizes the result with regard to relocation i.e. in border-areas, within the BSR or in a global perspective. Impacts on employment is evaluated as well the paper addresses witch branches in particular are at risk to loose economic weight in the BSR as a consequence of changes in the international division of labor.
Keywords: 330